FDG-PET reveals improved cardiac regeneration and attenuated adverse remodelling following Sitagliptin + G-CSF therapy after acute myocardial infarction. (29th September 2015) - Gross, Lisa; Paintmayer, Lisa; Lehner, Sebastian; Brandl, Lydia; Brenner, Christoph; Grabmaier, Ulrich; Huber, Bruno; Bartenstein, Peter; Theiss, Hans-Diogenes; Franz, Wolfgang-Michael; Massberg, Steffen; Todica, Andrei; et al.
Abstract: Aims: Dual therapy comprising G-CSF for mobilization of bone marrow-derived progenitor cells (BMPCs), with simultaneous pharmacological inhibition of dipeptidylpeptidase-IV for enhanced myocardial recruitment of circulating BMPC via the SDF-1α/CXCR4-axis, has been shown to improve survival after acute myocardial infarction (AMI). Using an innovative method to provide non-invasive serial in vivo measurements and information on metabolic processes, we aimed to substantiate the possible effects of this therapeutic concept on cardiac remodelling after AMI using 2-deoxy-2-[18F]fluoro- d -glucose positron emission tomography (FDG-PET). Methods and results: AMI was induced in C57BL/6 mice by performing surgical ligation of the left anterior descending artery in these mice. Animals were then treated with granulocyte-colony stimulating factor + Sitagliptin (GS) or placebo for a duration of 5 days following AMI. From serial PET scans, we verified that the infarct size in GS-treated mice ( n = 13) was significantly reduced at Day 30 after AMI when compared with the mice receiving placebo ( n = 10). Analyses showed a normalized FDG uptake on Day 6 in GS-treated mice, indicating an attenuation of the cardiac inflammatory response to AMI in treated animals. Furthermore, flow cytometry showed a significant increase in the anti-inflammatory M2-macrophages subpopulation in GS-treated animals. In comparing GS treated with placebo animals, those receiving GS-therapy showed a reduction in myocardial hypertrophy and left ventricular dilatation, which indicates the beneficial effect of GS treatment on cardiac remodelling. Remarkably, flow cytometry and immunohistochemistry showed an increase of myocardial c-kit positive cells in treated mice ( n = 12 in both groups). Conclusion: Using the innovative method of micro-PET for non-invasive serial in vivo measurements of metabolic myocardial processes in mice, we were able to provide mechanistic evidence that GS therapy improves cardiac regeneration and reduces adverse remodelling after AMI.